A study on the asset smart management system based on IOT - Han, Moonhee; Kim, Yousin; Soo Park, Hark; Ho Kim, Dae (International Journal of Engineering and Technology, 2018)
Background/Objectives: Most companies use a variety of assets for their operations. However, most companies use inefficient methods, such as on-the-spot inspections once or twice a year, instead of using the newest IT technology to manage their valuable assets. Furthermore, there is no pre-control and post-management system to prevent external leakage and the loss of expensive and portable assets.Methods/Statistical analysis: This study aims to study a practical and smart asset management system that can manage the real-time locations and the movement statuses of assets using the existing Radio-Frequency Identification (RFID) technology and the newest Bluetooth Low Energy (BLE) technology.Improvements/Applications: Through the Smart Asset Management System developed through this study, it was possible to improve the accuracy of assets due diligence and shorten the time, and provide asset position information to the manager in real time, thereby reducing the manpower, time and cost for asset management work. As a result of the study, a Smart Asset Management System (SAMS) was developed using two IoT technologies and the system was used for 11 months in the field. When the relevant system was applied to the field, there were some effects such as,the improvement in accuracy, the reduction in input manpower, the reduction in input time, and the reduction in the number of times of surveyscompared to past manual asset management.Â Â